Nursing Care in Schizophrenic Clients (Delusion) in Hospital Service Management: A Case Study - Eriyono Budi Wijoyo; Mustikasari Mustikasari (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2020)
Introduction: care for mental patients needs to be continuous and collaboration between health workers and the client's family is needed. This collaboration can be done by carrying out one of the complementary training activities to extend the recurrence time and prepare the client to return to the community. Objective: to find out schizophrenia nursing care in a hospital. Method: The process of writing this scientific article uses a case study approach with a descriptive method drawn from the life and personal experience of the author. To collect data in the form of articles, the author uses several databases, namely Science Direct and Google Search. The author also uses several search keywords such as "Psychiatric Disorder", "Perception Disorder", "Delusion", "Therapy Complementer", using the boolean "AND". In addition to using keywords, the author also uses inclusion and exclusion criteria starting from articles published 2010-2020, using Indonesian and English as well as fulltext articles with reliable sources. From the search above, thousands of articles were obtained and the authors analyzed and raised the title "Nursing Care for Schizophrenic Clients (Delusions) in Hospital Service Management: Case Studies". Results and Discussion: Clients in cases showing chronic schizophrenia with prominent symptoms are delusions. Clients with delusions can be done training or complementary therapy for the process of preparation for returning home and returning to the community. Conclusions and Recommendations: The nursing process in psychiatric patients especially chronic schizophrenia must be continuous and continuous. This severe mental disorder is chronic and there will be a recurrence so there is a need for cooperation between the nurse and the client's family for the implementation of therapy. Therapies such as music therapy, aromatherapy, massage, reflexology, animal therapy, cinema therapy, yoga and social skill training. Further research is needed related to the effects of complementary therapy associated with schizophrenia. Keywords: Nursing Care, Schizophrenia, service management, delusions